A Geometry-Based ISAC Channel Model for Vehicle-To-Vehicle Scenarios - Zhang, Guojin; Cai, Xuesong; Franchi, Norman; Lübke, Maximilian (2025 IEEE European Conference on Antennas and Propagation (EuCAP), 2025)
Integrated sensing and communication (ISAC) technique has recently gained significant attention in both academic and industrial sectors, as it can provide both sensing and communication functions using the same transmission and frequency spectrum. In this paper, a geometry-based statistical ISAC channel model for vehicle-to-vehicle (V2V) scenario is established, based on the ray-tracing simulation on the highway scenario at 77 GHz. An improved multipath-component-distance (MCD) threshold-based clustering algorithm is proposed to jointly group the paths for sensing and communication channels as clusters. These clusters are matched to the physical interaction objects in the scenarios. Based on the clustering results, cluster level parameters (i.e., intra-cluster delay, azimuth and Doppler spread) were explored. Furthermore, the clusters contributed from the same physical interaction object in both communication and sensing channels are regarded as ``sharing sensing clusters''. To investigate the correlation and differences between communication and sensing channel, shared degree (SD) metric is analyzed.<br

A Scatterer Localization Method Using Large-Scale Antenna Array Systems - Zhang, Guojin (2022 IEEE Conference on Antenna Measurements and Applications (CAMA), 2022)
As ultra-massive multiple-input multiple-output (UM-MIMO) has emerged as a key technology for millimeter-wave and terahertz communications, the spherical wave propagation should be considered for channel modeling. Therefore, it is critical to identify the locations and evolving behaviors of scatterers, i.e., the sources of the spherical wavefronts. In this contribution, a novel space-alternating generalized expectation-maximization (SAGE) based scatterer localization algorithm is proposed, where a large-scale antenna array is divided into multiple sub-arrays. Due to the decreased aperture of each sub-array, plane wave assumption can be applied to estimate the angles of departure/arrival, delays and amplitudes of multipath components (MPCs). Based on the angle variations of MPCs observed at different sub-arrays, the corresponding scatterers can be located. The proposed algorithm is verified in a simulation using a large-scale uniform circular array (UCA) system. Moreover, we apply this algorithm to an indoor measurement campaign conducted at 27-29 GHz in a hall scenario. Dominant scatterers are identified, which can be used for the development of further geometry-based stochastic channel models.<br
Keywords: Antenna measurements; Location awareness; Parameter estimation; Propagation; Millimeter wave technology; Stochastic processes; Delays; Large-scale antenna array; spherical wave propagation; scatterer localization; channel parameter estimation

A USRP-Based Channel Sounder for UAV Communications - Zhang, Guojin (2020 14th European Conference on Antennas and Propagation (EuCAP), 2020)
The unmanned-aerial-vehicle (UAV) has attracted great interests in both civil and military applications, due to its low cost, flexibility and ability to establish seamless coverage. In this paper, a Universal Software-defined Radio Peripheral (USRP) based channel sounding system for characterizing the UAV communication channel is introduced, which can be applied in both active and passive measurement campaigns. To investigate the effect of the equipment in the UAV measurement system, measurements were conducted by connecting two USRP devices directly with a cable. Furthermore, a post-processing method is proposed to calibrate the delay shift and “fake” Doppler frequency caused by the frequency deviation of the local oscillator in the system.<br
Keywords: Local oscillators; Position measurement; Real-time systems; Rail transportation; Frequency measurement; Delays; Doppler effect; unmanned-aerial-vehicle (UAV); channel sounding; delay shift; “fake” Doppler frequency; unmanned-aerial-vehicle (UAV); channel sounding; delay shift; and; fake; Doppler frequency

Dynamic Channel Modeling for Indoor Millimeter-Wave Propagation Channels Based on Measurements - Cai, Xuesong; Zhang, Guojin; Zhang, Chao; Fan, Wei; Li, Jinxing; Pedersen, Gert Frolund (IEEE Transactions on Communications, 2020)
In this contribution, a recently conducted measurement campaign for indoor millimeter-wave (mm-wave) propagation channels is introduced. A vector network analyzer (VNA)-based channel sounder was exploited to record the channel characteristics at the frequency band from 28–30 GHz. A virtual uniform circular array (UCA) with a radius of 0.25 m was formed using a rotator with 360 steps. Moreover, by taking advantage of fiber-optic technique applied in the channel sounder, measurements at 50 positions were performed from an indoor hall to an indoor corridor along a long pre-defined route. A low-complexity high-resolution propagation estimation (HRPE) algorithm is exploited to estimate the propagation parameters of multipath components (MPCs). Based on the HRPE estimation results, a novel clustering identification and tracking algorithm is proposed to trace clusters. Composite channel characteristics, cluster-level characteristics and dynamic (or birth-death) behaviours of the clusters are investigated, which constitute a dynamic model for the indoor mm-wave channel.<br
Keywords: Antenna measurements; Antenna arrays; Frequency measurement; Area measurement; Heuristic algorithms; 5G mobile communication; Attenuation; Millimeter-wave (mm-wave); parameter estimation; clustering; birth-death behavior; dynamic channel

Experimental Characterization of Millimeter-Wave Indoor Propagation Channels at 28 GHz - Zhang, Guojin; Saito, Kentaro; Fan, Wei; Cai, Xuesong; Hanpinitsak, Panawit; Takada, Jun-Ichi; Pedersen, Gert Frolund (IEEE Access, 2018)
The increasing requirement for the mobile data traffic accelerates the research of millimeterwave (mm-wave) for future wireless systems. Accurate characterization of the mm-wave propagation channel is fundamental and essential for the system design and performance evaluation. In this paper, we conducted measurement campaigns in various indoor scenarios, including classroom, office, and hall scenarios, at the frequency bands of 27-29 GHz. The spatial channel characteristics were recorded by using a large-scale uniform circular array. A high-resolution parameter estimation algorithm was applied to estimate the mm-wave spherical propagation parameters, i.e., the azimuth angle, elevation angle, delay, source distance, and complex amplitude of multipath components. With the same measurement system, the channel parameters including decay factor, delay spread, angular spread, and line of sight power ratio are investigated thoroughly in individual indoor scenarios and compared in different indoor scenarios. Furthermore, the impact of the furniture richness level and indoor geometry on the propagation parameters are also investigated.<br
Keywords: Antenna measurements; Delays; Frequency measurement; Transmitting antennas; Millimeter wave propagation; Wireless communication; Azimuth; Decay factor; delay spread; angular spread; LOS power ratio; millimeter-wave; channel sounding

Geometry-Based Clustering Characteristics for Outdoor Measurements at 28-30 GHz - Zhang, Guojin; Nielsen, Jesper Odum; Cai, Xuesong; Pedersen, Gert Frolund; Fan, Wei (IEEE Antennas and Wireless Propagation Letters, 2022)
This letter presents an analysis of channel characteristics for an outdoor scenario at the frequency band of 28–30 GHz. A geometry-based clustering algorithm is proposed to group the measured multipath components (MPCs) from the interaction points on the surrounding walls or objects according to ray-tracing three-dimensional (3-D) simulations, giving results that are more physically interpretable than the traditional clustering algorithms. The cluster-level characteristics at 15 positions along a predefined route covering both line-of-sight (LoS) and non-LoS (NLoS) scenarios are investigated. Moreover, power contributions of MPCs with multiple bounces (up to seven bounces in NLoS scenario) from the interaction objects are also investigated.<br
Keywords: outdoor measur ement; radio propagation; geometry-based clustering; Dispersion; millimeter wave (mm-wave); interaction objects (IOs)

Low Altitude Air-to-Ground Channel Characterization in LTE Network - Zhang, Guojin (13th European Conference on Antennas and Propagation, EuCAP 2019, 2019)
Keywords: graph modeling and path loss; LTE; Air-to-ground channel; channel measurements

Millimeter-Wave Channel Characterization in Large Hall Scenario at the 10 and 28 GHz Bands - Zhang, Guojin (13th European Conference on Antennas and Propagation, EuCAP 2019, 2019)
Keywords: Millimeter-wave; delay spread and angle spread; path loss

Modeling Multi-Frequency Characteristics for Classroom and Hall Scenarios at 2-4, 9-11 and 27-29 GHz Bands - Zhang, Guojin; Nielsen, Jesper Odum; Cai, Xuesong; Saito, Kentaro; Hanpinitsak, Panawit; Takada, Jun-Ichi; Pedersen, Gert Frolund; Fan, Wei (IEEE Access, 2021)
This paper investigates the wideband channel characteristics obtained in a classroom and a hall indoor scenarios at 2-4, 9-11 and 27-29GHz. A virtual uniform circular array (UCA) based channel sounding system was utilized to capture wideband spatial channel characteristics. The propagation parameters of multipath components (MPCs) were estimated by using a high resolution parameter estimation (HRPE) algorithm. The estimated MPCs are further grouped into clusters via a novel clustering identification algorithm based on the KPowerMeans algorithm. The comparison of the composite and cluster-level characteristics at multiple frequency bands in both scenarios is investigated. Moreover, the impact of the indoor room environment, i.e. dimension and furniture, on the propagation channel is also analyzed. The statistics of channel parameters at multiple frequency bands extracted constitute a stochastic clustered spatial channel model.<br
Keywords: Parameter estimation; Azimuth; Clustering algorithms; Reflection; Delays; Spatial resolution; Wideband; Multi-frequency bands propagation; clustering; channel sounding; channel measurement; channel estimation

On Efficient Non-Stationary Channel Emulation in Conductive Phase Matrix Setup for Massive MIMO Performance Testing - Zhang, Guojin (IEEE Transactions on Vehicular Technology, 2022)
Massive multiple-input multiple-output (MIMO) is considered as a critical technique in 5 G New Radio (NR), due to its capability to significantly improve data rate and link reliability for the radio link. To make it a reality, it is essential to evaluate massive MIMO performance in realistic spatial fading channel conditions. Specifically, dynamic spatial channel emulation is crucial to evaluate the massive MIMO beam operations. Due to the high cost associated with both the traditional conduced testing method and the standardized multi-probe anechoic chamber (MPAC) based Over-the-Air (OTA) testing setup for massive MIMO performance testing, fading channel emulation for massive MIMO testing using a conductive phase matrix setup has been proposed in the literature. However, it is still a challenging problem to emulate dynamic spatial channels in a cost-effective and efficient manner for the conductive phase matrix setup, since traditional algorithms suffer from high computational complexity and system cost. This paper proposes a fast and accurate framework to emulate dynamic spatial channels in the phase matrix setup, where the basic idea is to mimic a virtual MPAC setup. By doing so, we can mimic MPAC setup with flexible probe configurations. Furthermore, a novel successive cancellation strategy and a closed-form algorithm are proposed to determine the probe locations and probe weights, respectively, which can significantly reduce the computational complexity associated with dynamic channel emulation. Simulation results show that the proposed algorithm is highly accurate and computationally efficient, compared to state-of-art solutions. Further, we apply our developed algorithm to emulate measured non-stationary channels and excellent emulation accuracy can be achieved. The proposed method can be employed for emulating dynamic spatial channels, which is of great importance for massive MIMO performance testing.<br
Keywords: Probes; Testing; Massive MIMO; Emulation; Heuristic algorithms; Vehicle dynamics; Antennas; Channel emulation; massive MIMO; phase matrix; virtual over-the-air testing; virtual probe